2009
DOI: 10.1523/jneurosci.2521-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3F Is a Bifunctional Guidance Cue for Dopaminergic Axons and Controls Their Fasciculation, Channeling, Rostral Growth, and Intracortical Targeting

Abstract: Dopaminergic neurons in the mesodiencephalon (mdDA neurons) make precise synaptic connections with targets in the forebrain via the mesostriatal, mesolimbic, and mesoprefrontal pathways. Because of the functional importance of these remarkably complex ascending axon pathways and their implication in human disease, the mechanisms underlying the development of these connections are of considerable interest. Despite extensive in vitro studies, the molecular determinants that ensure the perfect formation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 76 publications
6
138
0
Order By: Relevance
“…Moreover, mDA neurons start extending neurites dorsally, at E11.5 (Blakely et al, 2011;Kolk et al, 2009), but they soon turn ventrally, towards the meninges, and form the medial forebrain bundle (MFB). In the present study, we first found that VM meninges regulate axonal bundling in organotypic cultures and found CXCR4 phosphorylation in mDA processes at different stages of development, suggestive of an in vivo function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mDA neurons start extending neurites dorsally, at E11.5 (Blakely et al, 2011;Kolk et al, 2009), but they soon turn ventrally, towards the meninges, and form the medial forebrain bundle (MFB). In the present study, we first found that VM meninges regulate axonal bundling in organotypic cultures and found CXCR4 phosphorylation in mDA processes at different stages of development, suggestive of an in vivo function.…”
Section: Discussionmentioning
confidence: 99%
“…After two washes in TBS and a brief wash in 50 mM Tris-HCl, pH 7.6, sections were reacted with a solution containing 0.035% DAB and 0.015% hydrogen peroxide in 50 mM Tris-HCl for 15 min at RT. The reaction was terminated by several washes in 50 mM Tris-HCl and sections were mounted in glycerol 69,70 . Sections incubated with AlexaFluor antibodies were counterstained with either fluorescent Nissl (NeuroTrace; Invitrogen) or 4 0 ,6-diamidino-2-phenylindole (DAPI) (Sigma), washed extensively in PBS and embedded in 90% glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, netrin signalling via the deleted colorectal cancer (DCC) receptor, which is known to actively regulate axonal growth (Round and Stein 2007), has been strongly implicated in the formation of the VM DA circuitry (Xu et al 2010;Flores et al 2005;Manitt et al 2011;Lin et al 2005;Sgado et al 2012;Vitalis et al 2000). Additionally, signalling between Slits and their Robo receptors (Bagri et al 2002;Dugan et al 2011;Lin et al 2005;LopezBendito et al 2007), and by semaphorins (HernandezMontiel et al 2008;Torre et al 2010;Tamariz et al 2010;Kolk et al 2009), has been shown to regulate the formation of DA projections from the VM to the striatum. These identified molecules are well-established regulators of axonal growth and guidance in other regions of the nervous system.…”
Section: Introductionmentioning
confidence: 99%